The Effectiveness of Differentiated Instruction in Elementary School Subject: Teachers’ Perceptions - Efendi, Ulfah Putri; Wibowo, Setiawan Edi; Sartono, Emmanuel Kus Eddy; Lena, Mai Sri (FKIP Universitas Lampung, 2024)
The Effectiveness of Differentiated instruction in Elementary School Subject: Teachers’ Perceptions. Objectives: This study aims to explore teachers’ perceptions of differentiated instruction in the Pancasila Education subject in Elementary Schools and its impacts, benefits, and challenges. Methods: The data collection was conducted by using a survey method by distributing the questionnaires to 801 respondents followed by semi-structured interviews. Furthermore, the data were analyzed by using the quantitative descriptive analysis techniques and Spearman correlation tests to determine the relationship between the implementation of differentiated instruction and the aspects of teachers’ perceptions. Meanwhile, the results of the interviews were analyzed by using a descriptive qualitative approach. The elementary school subject referred to in this study is Pancasila Education. Findings: The results of the study indicated that the teachers have implemented the differentiated instruction in the Pancasila Education subject through differentiation of content, process, and product. Furthermore, the differentiated instruction was able to meet the students’ learning needs and improve motivation, participation, and learning outcomes in the Pancasila Education subject in Elementary Schools. The teachers overcame the problems in adopting differentiated instruction, including lack of understanding of this approach, difficulty in conducting diagnostic testing and high number of students. Conclusion: The differentiated instruction in teachers' perceptions can help improve the students' motivation, participation, and learning outcomes. In addition, it also helps teachers in meeting their students' learning needs. Keywords: perception, differentiated learning, pancasila education, elementary school.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024121